A Mach-Zehnder interferometer by combining a microtaper with a long period grating in an all solid photonic bandgap fiber and its temperature sensing characteristic - Wu, Zhifang (2013)
We demonstrate a new type of Mach-Zehnder interferometer by combining a nonadiabatic microtaper with a long period grating in the same stage of all solid photonic bandgap fibers. Meanwhile, the mode-coupling caused by the microtaper is indirectly verified by the interference with the long period grating, which is designed for the resonance between the fundamental core mode and LP01 cladding supermodes. Finally, the temperature response is also reported.